Analysis of the Influence of Ewom on Purchase Intention Mediated by Brand Image - Apriyanti, Nike; Sriwijayanti, Hari; Bella, Shinta (Jurnal Informatika Ekonomi Bisnis, 2026)
This research was conducted to understand the influence of Ewom on purchasing interest mediated by Brand Image. The more specific aim of this research is to analyze the influence of eWOM on purchase intention mediated by Brand Image (case study of iPhone users in the city of Padang. The research was conducted on 80 samples of iPhone users in the City of Padang as purposive sampling, and the data analysis method used SmartPLS Version 3.0 to test the relationship of influence in the SEM model. The results of the research obtained are that eWOM has a direct effect on buying interest which is mediated by Brand Image, while eWOM has a direct effect on Brand Image and Brand Image has a direct effect on buying interest. Brand Image is a mediation between eWOM and buying interest, thus totally strengthening this influence. The path that states the strongest influence relationship is that eWOM has a positive effect on brand image by 38% and then has a positive effect on buying interest by 29% and the rest is influenced by other indicators.